Study on Deformation of CVT Pulleys at High Speeds - Xiang Hongwei; Gu Qianwei; Chen Huiling; Wang Zhiming; Peng Tao (Jixie chuandong)
Under the condition of high speed, the deformation of the pulley will cause the metal strip to shift along the cone of the pulley, which will aggravate the wear between the various parts of the CVT, which will seriously affect the service life and transmission efficiency of the CVT. Therefore, the mechanical model of the pulley under the condition of high speed was established, the influence of speed ratio, torque, speed and other factors on the axial deformation of the CVT pulley was analyzed by using the finite element method, and the test was verified. The results show that the axial deformation of the pulley decreases with the increase of the speed ratio, and decreases first and then increases with the increase of torque and speed, and the test results are consistent with the analysis results.